Curriculum as praxis: Ensuring quality technical education in Singapore for the 21st century. - Yek, Tiew Ming; Penney, Dawn (Education Policy Analysis Archives, 2006)
Singapore, a small island city-state, has achieved notable economic advancement within 40 years since independence. It is fast becoming a global city and a knowledge society. In education and training, the Singapore system has evolved from its British roots. Macro performance indicators of participation rate, literacy rate and mean years of schooling, show that the current education system can be regarded as highly successful. The contributions of general education as well as technical education and training to the overall success of the nation are often cited. Technical education and training, which is globally perceived as having a lower status than "academic" curricula, has largely overcome its "image" problem in Singapore. Singaporeans have seemingly embraced technical education and training as an accessible, attractive mode of education, which therefore enjoys a high participation rate. The success and quality of technical education and training were affirmed when its main provider, the Institute of Technical Education, became the first educational institution in Singapore to win the Singapore Quality Award in October 2005. This paper provides a review of the contemporary education system and curriculum in Singapore with a focus on technical education and training vis-à-vis a vision of education and training in and for postmodern knowledge societies. Suggestions are made on how the technical education and training sector in Singapore can further develop and thrive in the 21st century, while continuing to be accessible and of high quality.